Social enterprises in Argentina : a critical approach to understand the hybrid landscape - Blugerman, Leopoldo Ernesto (2022)
[From the introduction:] This paper provides an overview of my research submitted for the award of the “PhD by Published Work” (presented in the second part of this submission) and constitutes the required “supporting document (of up to 10,000 words) contextualising the submission and explaining in an introduction and conclusion the importance of the contribution to scholarship of the published works.” The document starts with my research objective and research questions, then a clarification of my organisational focus and context, followed by the body-of worksubmitted section. Next come my theoretical approaches and methodology. A following section on how my submitted papers addressed the research questions. Finally, the conclusion, and gaps and directions for future research. It should be noted that my published work and reflections are also influenced by my experience as an instructor in undergraduate and postgraduate programs (both in Argentina and abroad), a consultant (for social enterprises, firms, international organisations, and public agencies), and member of INAES’ Advisory Council.
HydraID: hull:18692 Hydra Discover Access Group: public ETD Collection: ETDBusinessSchool
Keywords: Systems science